ANALYSIS OF ELEMENTARY SCHOOL STUDENTS' NUMERATION ERRORS AT EACH STAGE OF POLYA PROBLEM SOLVING IN SOLVING MATHEMATICS STORY PROBLEMS - Nurhasanah, Aan; Syafari, Rahayu (Journal Of Educational Experts (JEE), 2026)
This study aims to analyze students’ numeracy errors in solving contextual mathematical problems based on Polya’s problem-solving stages and numeracy literacy framework. The research employed a qualitative descriptive approach by analyzing students’ written responses to a contextual problem involving calculation of total purchase cost. Data were analyzed using Polya’s four stages: understanding the problem, devising a plan, carrying out the plan, and looking back. The findings revealed that students’ errors predominantly occurred in the early stages of problem solving, particularly in understanding the problem and devising a solution strategy. Students demonstrated partial identification of relevant information and showed difficulties in mathematical modelling, especially in connecting unit price concepts with quantity relationships. Despite these difficulties, students exhibited adequate procedural skills during arithmetic calculations. However, metacognitive reflection was absent, as students did not verify or evaluate their solutions. These findings suggest that numeracy difficulties are more closely related to conceptual understanding and modelling processes rather than computational skills. The study highlights the importance of instructional approaches that emphasize contextual interpretation, mathematical modelling, and reflective thinking to enhance students’ numeracy literacy